3(1-2x)-5(3x)-6(3x-4)=83

Simple and best practice solution for 3(1-2x)-5(3x)-6(3x-4)=83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-2x)-5(3x)-6(3x-4)=83 equation:


Simplifying
3(1 + -2x) + -5(3x) + -6(3x + -4) = 83
(1 * 3 + -2x * 3) + -5(3x) + -6(3x + -4) = 83
(3 + -6x) + -5(3x) + -6(3x + -4) = 83

Remove parenthesis around (3x)
3 + -6x + -5 * 3x + -6(3x + -4) = 83

Multiply -5 * 3
3 + -6x + -15x + -6(3x + -4) = 83

Reorder the terms:
3 + -6x + -15x + -6(-4 + 3x) = 83
3 + -6x + -15x + (-4 * -6 + 3x * -6) = 83
3 + -6x + -15x + (24 + -18x) = 83

Reorder the terms:
3 + 24 + -6x + -15x + -18x = 83

Combine like terms: 3 + 24 = 27
27 + -6x + -15x + -18x = 83

Combine like terms: -6x + -15x = -21x
27 + -21x + -18x = 83

Combine like terms: -21x + -18x = -39x
27 + -39x = 83

Solving
27 + -39x = 83

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + -39x = 83 + -27

Combine like terms: 27 + -27 = 0
0 + -39x = 83 + -27
-39x = 83 + -27

Combine like terms: 83 + -27 = 56
-39x = 56

Divide each side by '-39'.
x = -1.435897436

Simplifying
x = -1.435897436

See similar equations:

| 4+9=5 | | 28y=32y+2 | | 32+6x=12-8.5 | | -5a+12+7a=2a-4a | | x^3-4x^2-14x-14=0 | | 9x+7=-38 | | 3a+7=b | | 3xa+7=b | | 20x^2+52x-24=0 | | 6t-t-3=4t-8 | | 176-y=253 | | (2e^2-5e)+(7e-3e^2)= | | 25x^4+259x^2+400=0 | | 3x+76.5= | | x+12y+16=0 | | .6x+.1y=.5 | | f(a+4)=6x+7 | | 4-6x=5-9 | | (t+4)(t+4)=54 | | -27x=81 | | 142.5*20=91 | | 142.5*91=20 | | x=400+-1y | | 6x+18=12-9 | | 142.5*91=20*x | | 8x+21=6x+69 | | 2x-4=7x-7-5x | | 142.5=20*91 | | 4x+35=14x+45 | | 0.7x=0.9+0.2x | | -4+2x=-8+24 | | 7y+10=2y+25 |

Equations solver categories